The Effect of Impact Loading on the Various Properties of Improved Non-Reinforced Masonry Elements by Utilizing Flexible Fiber-Reinforced Concretes - Seyedmohammad Amini; Alireza Mirjalili; Mohammadreza Javaheri (Migration Letters, 2023)
The utilization of flexible fiber-reinforced concretes, including engineered cementitious composites (ECCs), to retrofit unreinforced masonry walls is crucial due to their brittle behavior and limited flexibility. In this context, it is essential to consider how well such materials perform when utilized as a reinforcement layer for unreinforced masonry walls to enhance their behavior (flexibility and strength) when subjected to dynamic stresses, notably impact loads. Through nonlinear dynamic impact analysis, the current research assesses and compares the vertical middle displacement, energy, and distribution of plastic strains in unreinforced masonry materials under two conditions, i.e., non-retrofitted and retrofitted with a one- or two-side cover of ECC layers under dynamic impact loading. The ECC reinforcing layers thickness, stiffness, and placement location of middle or sides of the top surface with full connection were changed to examine the vertical displacement, Energy dissipation and plastic strains distribution of the non-reinforced masonry specimen during the vertical impact loading. Introducing ECC layers to unreinforced masonry materials enhanced their behavior against out-of-plane impact loads, dissipated energy, and minimized plastic strains and cracks.